Age-Based Disparities in Metastatic Melanoma Patients Treated in the Immune Checkpoint Inhibitors (ICI) Versus Non-ICI Era: A Population-Based Study - Safi, Mohammed; Al-Azab, Mahmoud; Jin, Chenxing; Trapani, Dario; Baldi, Salem; Adlat, Salah; Wang, Aman; Ahmad, Bashir; Al-madani, Hamza; Shan, Xiu; Liu, Jiwei (Frontiers in Immunology, 2021)
Immune checkpoint inhibitors (ICIs) have revolutionized metastatic melanoma treatment, but our knowledge of ICI activity across age groups is insufficient. Patients in different age groups with advanced melanoma were selected based on the ICI approval time in this study. Patients with melanoma were identified in the Surveillance, Epidemiology, and End Result (SEER) database program 2004-2016. The results showed that 4,040 patients had advanced melanoma before the advent of ICI (referred to as the "non-ICI era"), whereas 6,188 cases after ICI (referred to as the "ICI era"). In all age groups, the cases were dominated by men. The differences between the first (20–59 years) and second (60–74 years) age groups in both eras were significant in terms of surgery performance and holding of insurance policies (P 0.05). The first and second groups (20-59 and 60-70) showed no difference in survival (median months: 8) during the non-ICI era, but the difference is evident in the ICI era age groups, with the younger group (20-59) having significantly better survival (P=0.0001, median months:18,14,10) respectively. Multivariate analysis of the first group (the youngest) in the ICI era revealed that surgery was significantly associated with an increase in survival among patients compared with those who did not undergo surgery (P = < 0.0001).Furthermore, having an insurance policy among all age groups in the ICI era was associated with favorable survival in the first and second age groups (20-59) and (60-74) (P = 0.0001) while there were no survival differences in the older ICI group (> 74). Although there is a difference in survival between the ICI era and the non-ICI era, these results demonstrate that ICI positively affected the survival of younger patients with advanced melanoma (first age group) than it had beneficial effects on older patients. Moreover, having performed cancer surgery and holding an insurance policy were positive predictors for patient survival. This study emphasizes that adequate clinical and preclinical studies are important to enhance ICI outcomes across age groups.